2010
DOI: 10.5468/kjog.2010.53.5.449
|View full text |Cite
|
Sign up to set email alerts
|

A case of acardiac twin pregnancy with fetus survival after successful radiofrequency ablation of umbilical cord

Abstract: Acardiac twin is a rare anomaly that occurs 1% in monochorionic twins and 1 in 35,000 pregnancies overall. Acardiac twin, also known as twin-reversed arterial perfusion (TRAP) sequence, involves a "pump" or donor twin perfusing a recipient or "acardiac" twin through vascular (usually arterial-arterial and venous-venous) anastomoses. Perinatal mortality rate for the pump twin has been reported to be 50~75%, mainly as a result of polyhydramnios, preterm labor, and congestive heart failure. Therefore, occlusion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In 2004, Lee et al [12] reported the use of intra-abdominal alcohol ablation. Another case, which was treated using RFA, was reported by Jang et al [13] in 2010. The use of intrafetal RFA to treat the TRAP sequence, which is the most recently reported technique, was first reported in 2002 [9].…”
Section: Discussionmentioning
confidence: 99%
“…In 2004, Lee et al [12] reported the use of intra-abdominal alcohol ablation. Another case, which was treated using RFA, was reported by Jang et al [13] in 2010. The use of intrafetal RFA to treat the TRAP sequence, which is the most recently reported technique, was first reported in 2002 [9].…”
Section: Discussionmentioning
confidence: 99%